Pendekatan Rehabilitatif terhadap Narapidana Perempuan Lanjut Usia di Lapas Perempuan Kelas IIA Sungguminasa: Implikasi bagi Kebijakan Pemasyarakatan - Lumba Rego, Geby; Sudirman, Muh.; Wahyudi Gani, Andika (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2025)
This study aims to determine: (1) To find out how the implementation of the rehabilitative approach to elderly female prisoners at Class II A Sungguminasa Penitentiary. (2) To find out what are the challenges in implementing the rehabilitative approach for elderly female prisoners at Class II A Sungguminasa Penitentiary. This type of research is a case study research using a descriptive approach. Data collection techniques used include: observation, interviews, and documentation. The data obtained from the research results were processed using descriptive qualitative data analysis. The results of this study indicate that: (1) The implementation of the rehabilitative approach for elderly female prisoners is a psychosocial approach that aims to improve the psychological and social aspects of prisoners, the implementation includes screening and initial assessment, social rehabilitation services, and final assessment. Then regarding the guidance that has referred to the regulations for prisoner guidance in force in Indonesia, the guidance that applies in Correctional Institutions is personality and independence guidance. However, in the implementation of this guidance, it is adjusted to the conditions and abilities of the elderly prisoners themselves. (2) the challenges faced in the implementation of the rehabilitation program for the elderly, namely physical limitations are one of the main challenges faced in the rehabilitation program, many prisoners have difficulty following programs that require more intense physical activity or require extra energy. Limited infrastructure and facilities are also one of the challenges in rehabilitation, although they are adequate, but the limitations of overcrowding (excess residents) cause some facilities to not be fully adjusted to the needs of elderly prisoners.